"Northeast is a fiction. Northeast never existed": The northeastern migrant and the diaspora experience in Belchior's songs (Orfeu, 2023)
The purpose of this article is to explore the narrative of the northeastern migrant and how Antônio Carlos Belchior's diasporic perspective is associated with his way of creating and representing the world from his own experiences as a migrant subject. For this, the songs Passeio (1974), Fotografia 3x4 (1976) and Conheço o Meu Lugar (1979) will be analyzed and part of the artist's trajectory, from an empirical apprehension of the song (TATIT, 2003) and an associated interpretation literary anthropology (ISER, 2013).